Webbing Barklouse, Psocid (unofficial common names), Archipsocus nomas Gurney (Insecta: Psocoptera: Archipsocidae) - Donald W. Hall; Jerry F. Butler (EDIS)
Archipsocus nomas Gurney is a communal web-spinning barklouse. During some years they make extensive silken webs that often cover the trunks and branches of trees in the southeastern U.S. The webs are believed to protect the barklice from predators. The webs are unsightly, but neither the barklice nor the webs cause any harm to the trees. This document is EENY-275, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2002.